2020
DOI: 10.1108/ijlls-04-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ educational beliefs change through lesson study: implications for school culture

Abstract: PurposeThe study aims at exploring the perspective of three English as a Foreign Language teachers after their year-long involvement in the Lesson Study project in the context of Kazakhstan in order to capture and list any perceived changes in teachers’ educational beliefs over the period of the Lesson Study intervention. The main argument of the study suggests that the school-based Lesson Study initiative is conducive to triggering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In addition, our study procedure showed that the LS team members' active engagement in utilizing the LS and OA innovations through implementing change in their classroom practice has had a positive impact on them to rethinking their teaching practice, on their attitudes to students, and about their learning tasks when it comes to improving mathematical reasoning habits, collegiality, and professional selfidentification. This implication is supported by Khokhotva and Albizuri (2020) who found that the LS framework has enormous potential regarding facilitating change in teachers' educational beliefs. These changes are associated with establishing a more positive student-centered teaching approach and encouraging a rights-based school culture in which teachers share their vision and increasing the capacity for innovation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, our study procedure showed that the LS team members' active engagement in utilizing the LS and OA innovations through implementing change in their classroom practice has had a positive impact on them to rethinking their teaching practice, on their attitudes to students, and about their learning tasks when it comes to improving mathematical reasoning habits, collegiality, and professional selfidentification. This implication is supported by Khokhotva and Albizuri (2020) who found that the LS framework has enormous potential regarding facilitating change in teachers' educational beliefs. These changes are associated with establishing a more positive student-centered teaching approach and encouraging a rights-based school culture in which teachers share their vision and increasing the capacity for innovation.…”
Section: Discussionmentioning
confidence: 85%
“…The results might be of value for school leaders, educators, teacher trainers, and policymakers in terms of advocating OA being incorporated into the LS framework as a systematic approach to whole-school enhancement. This would act as a tool to encourage positive change in school culture, as well as give stimulus to future studies involving the school culture perspective about developing LS and OA impact evaluation tools (Khokhotva & Albizuri, 2020). However, this requires a thorough understanding of the details of LS (Inprasitha, 2011) and OA (Nohda, 2000) concepts, while teachers are planning and implementing OA treatment in the LS process.…”
Section: Discussionmentioning
confidence: 99%
“…Both LS and CLS have proved effective for promoting teachers' PD. Their positive effects include increased teaching knowledge (Lewis and Hurd, 2011), improved teacher beliefs (Khokhotva and Albizuri, 2020), enhanced teaching practice (Angelini and Alvarez, 2018), cognitive, emotional and social development (Alwadi et al, 2020), enhanced learner outcomes (Lin, 2020) and mediated curriculum implementation and innovation (Goh and Fang, 2017). However, studies investigating the role of CLS in language subjects are limited in number (Fang and Wang, 2021).…”
Section: Chinese Lesson Study As An Effective Pd Strategymentioning
confidence: 99%
“…There are studies conducted showing that collaborative work supports teachers' knowledge and appreciation for subject content development and teachers are satisfied with the way PLC support their professional growth towards leadership in their schools (Gunning et al, 2020). Teachers who implement leadership through changes in their practices in the classroom have a positive impact on teachers, for instance they are able to rethink their teaching practices, attitudes towards students and their learning and their professional level (Khokhotva & Albizuri, 2020). There are also research findings that suggest that key components of PLC should include elements of collective focus on student learning, reflective dialogue, and shared and supported leadership because they have a significant and positive relationship with teachers' level of professional practice .…”
Section: Competency Enhancement In Plc Implementationmentioning
confidence: 99%